Nursing Exposure to Bisphenols as a Cause of Male Idiopathic Infertility - Fenclová, Tereza; Řimnáčová, Hedvika; Chemek, Marouane; Havránková, Jiřina; Klein, Pavel; Králíčková, Milena; Nevoral, Jan (Frontiers in Physiology, 2022)
Idiopathic infertility is a serious problem, which can be caused and explained by exposure to endocrine disruptors, such as bisphenols. In our study, we studied translactational exposure to bisphenol and its effects on newborn male mice throughout their reproductive life. Newborn male mice were exposed to bisphenol S and bisphenol F through maternal milk from post-natal day 0 to post-natal day 15 at concentrations of 0.1 ng.g/bw/day and 10 ng.g/bw/day, respectively. Although there were minimal differences between the control and experimental groups in testicular tissue quality and spermatozoa quality, we discovered an interesting influence on early embryonic development. Moderate doses of bisphenol negatively affected cleavage of the early embryo and subsequently, the blastocyst rate, as well as the number of blastomeres per blastocyst. In our study, we focused on correlations between particular stages from spermatogenesis to blastocyst development. We followed epigenetic changes such as dimethylation of histone H3 and phosphorylation of histone H2 from germ cells to blastocysts; we discovered the transfer of DNA double-strand breaks through the paternal pronucleus from spermatozoa to blastomeres in the blastocyst. We elucidated the impact of sperm DNA damage on early embryonic development, and our results indicate that idiopathic infertility in adulthood may have causes related to the perinatal period.